Inventing safe sport: Comparing Swiss and global strategies - Benjamin Carr (Bern Open Publishing, 2024)
The revelations from the Magglingen Protocols article (Gertsch & Krogerus, 2020) brought a spotlight of Switzerland's national attention to the issues concerning safeguarding against maltreatment in sport. The experiences of the athletes featured in the article were certainly not the first, nor the last, of their kind in Switzerland, and much less in the world. While the International Olympic Committee provided guidelines for international federations and national Olympic committees to follow in the development of their own safeguarding programs (Burrows, 2017), the implementation of such programs varies considerably. Few, if any, in the emerging field would claim to have found the "right" way to handle the many facets of safeguarding, which are complexified by sociocultural norms and definitions, sport-specific practices, and local jurisprudence. Questions about who within the sports ecosystem is responsible, and for what, in the safeguarding process lack consensus, and countries have answered them in their own ways. Fundamentally, the philosophical notions of what constitutes "abuse," "maltreatment," "care," and "wellbeing" (among others) underpin any attempt to understand the safeguarding problem and respond to it with policy. The cultural differences in the meanings behind these notions leads consequently to the dissimilar implementation of efforts to address them. This presentation proposes a critical reflection on the strategic efforts globally and within Switzerland to understand and frame the issue of safeguarding to create a unified approach in policy making. While not an exhaustive comparison of every nation's approach, the reflection will compare the Swiss strategy with certain notable examples, highlighting what pressing moral and philosophical questions the Swiss strategy has yet to answer. References Burrows, K. (2017). IOC Safeguarding Toolkit for IFs and NOCs. International Olympic Committee. https://d2g8uwgn11fzhj.cloudfront.net/wp-content/uploads/2017/10/18105952/IOC_Safeguarding_Toolkit_ENG_Screen_Full1.pdf Gertsch, C., & Krogerus, M. (2020, October 31). Die Magglingen Protokolle. Tages-Anzeiger Das Magazin. https://www.tagesanzeiger.ch/wie-turnerinnen-in-magglingen-gebrochen-werden-170525604713